Interleukin‐6 and thrombopoietin concentrations in dogs with carcinoma with and without thrombocytosis. (8th December 2021) - Cheney, Adrienne; Woolcock, Andrew D.; Mukhopadhyay, Abhijit; Knapp, Deborah; Moore, George E.
Abstract: Background: Carcinoma‐associated thrombocytosis involves tumor production of mediators such as interleukin‐6 (IL‐6) and thrombopoietin (TPO) that increase thrombopoiesis and may play a role in tumor evasion and metastasis. Carcinoma‐associated thrombocytosis is described in people, but has not been described in dogs. Hypothesis/Objectives: Evaluate the concentrations of IL‐6 and TPO in dogs diagnosed with carcinoma with or without thrombocytosis. We hypothesized that IL‐6 and TPO concentrations would be higher in dogs with carcinoma compared to healthy dogs, and that IL‐6 and TPO concentrations would be higher in dogs with carcinoma and thrombocytosis when compared to dogs with carcinoma and normal platelet counts. Animals: One‐hundred sixteen dogs: 63 with carcinoma and 53 healthy control dogs. Methods: Complete blood count was performed in all dogs, and they were stratified for sub‐group analysis based on the presence or absence of thrombocytosis (platelet count > 500 103/µL). Serum TPO and IL‐6 concentrations were measured by ELISA. Results of selected numeric variables were compared using Wilcoxon rank sum tests for pairwise comparisons. A value of P < .05 was considered significant. Results: Twelve of the dogs with carcinoma (12/63, 19.0%) and none of the healthy control dogs (0%) had thrombocytosis. Thrombopoietin concentrations (median [range]) were significantly higher in dogs with carcinoma when compared to controls (87.42 pg/mL [0 to >600] vs 15.99 pg/mL [0 to >600], P  < .001). Interleukin‐6 concentrations (median [range]) were not different between dogs with carcinoma and healthy control dogs (9.70 pg/mL [0‐181.53] vs 3.03 pg/mL [0‐280.77], P  = .15). In dogs with carcinoma, the TPO and IL‐6 concentrations were not different between dogs with thrombocytosis and dogs with normal platelet count. Conclusions and Clinical Importance: Thrombopoietin concentrations were significantly higher in dogs with carcinoma, regardless of platelet count. Thrombopoietin is likely to be 1 of multiple factors that can impact platelet number, production, and consumption in dogs with carcinoma.